Arachidonic Acid Stress Impacts Pneumococcal Fatty Acid Homeostasis - Eijkelkamp, Bart A.; Begg, Stephanie L.; Pederick, Victoria G.; Trapetti, Claudia; Gregory, Melissa K.; Whittall, Jonathan J.; Paton, James C.; McDevitt, Christopher A. (Frontiers in Microbiology, 2018)
Free fatty acids hold dual roles during infection, serving to modulate the host immune response while also functioning directly as antimicrobials. Of particular importance are the long chain polyunsaturated fatty acids, which are not commonly found in bacterial organisms, that have been proposed to have antibacterial roles. Arachidonic acid (AA) is a highly abundant long chain polyunsaturated fatty acid and we examined its effect upon Streptococcus pneumoniae. Here, we observed that in a murine model of S. pneumoniae infection the concentration of AA significantly increases in the blood. The impact of AA stress upon the pathogen was then assessed by a combination of biochemical, biophysical and microbiological assays. In vitro bacterial growth and intra-macrophage survival assays revealed that AA has detrimental effects on pneumococcal fitness. Subsequent analyses demonstrated that AA exerts antimicrobial activity via insertion into the pneumococcal membrane, although this did not increase the susceptibility of the bacterium to antibiotic, oxidative or metal ion stress. Transcriptomic profiling showed that AA treatment also resulted in a dramatic down-regulation of the genes involved in the fatty acid biosynthesis, in addition to impacts on other metabolic processes, such as carbon-source utilization. Hence, these data reveal that AA has two distinct mechanisms of perturbing the pneumococcal membrane composition. Collectively, this work provides a molecular basis for the antimicrobial contribution of AA to combat pneumococcal infections